Psychological Correlates of Sexual Dysfunction in Female Rectal and Anal Cancer Survivors: Analysis of Baseline Intervention Data. (3rd April 2013) - Philip, Errol J.; Nelson, Christian; Temple, Larissa; Carter, Jeanne; Schover, Leslie; Jennings, Sabrina; Jandorf, Lina; Starr, Tatiana; Baser, Ray; DuHamel, Katherine
Abstract Introduction Sexual dysfunction represents a complex and multifactorial construct that can affect both men and women and has been noted to often deteriorate significantly after treatment for rectal and anal cancer. Despite this, it remains an understudied, underreported, and undertreated issue in the field of cancer survivorship. Aim This study examined the characteristics of women enrolled in an intervention trial to treat sexual dysfunction, and explored the relationship between sexual functioning and psychological well‐being. Methods There were 70 female posttreatment anal or rectal cancer survivors assessed as part of the current study. Participants were enrolled in a randomized intervention trial to treat sexual dysfunction and completed outcome measures prior to randomization. Main Outcomes Measures The main outcome measures are quality of life (QOL) (European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire [EORTC‐QLQ‐C30] and Colorectal Cancer‐Specific Module [QLQ‐CR38]), sexual functioning (Female Sexual Functioning Index), and psychological well‐being (Brief Symptom Inventory Depression/Anxiety, Impact of Events Scale‐Revised, CR‐38 Body Image). Results Women enrolled in the study intervention were on average 55 years old, predominantly Caucasian (79%), married (57%), and a median of 4 years postprimary treatment. For those reporting sexual activity at baseline (N = 41), sexual dysfunction was associated with a range of specific measures of psychological well‐being, all in the hypothesized direction. The Sexual/Relationship Satisfaction subscale was associated with all measures of psychological well‐being (r = −0.45 to −0.70, all P < 0.01). Body image, anxiety, and cancer‐specific posttraumatic distress were notable in their association with subscales of sexual functioning, while a global QOL measure was largely unrelated. Conclusions For sexually active female rectal and anal cancer survivors enrolled in a sexual health intervention, sexual dysfunction was significantly and consistently associated with specific measures of psychological well‐being, most notably Sexual/Relationship Satisfaction. These results suggest that sexual functioning may require focused assessment by providers, beyond broad QOL assessments, and that attention to Sexual/Relationship Satisfaction may be critical in the development and implementation of interventions for this cohort of patients. Philip EJ, Nelson C, Temple L, Carter J, Schover L, Jennings S, Jandorf L, Starr T, Baser R, and DuHamel K. Psychological correlates of sexual dysfunction in female rectal and anal cancer survivors: Analysis of baseline intervention data. J Sex Med 2013;10:2539–2548.